2010
DOI: 10.1182/blood-2009-02-207118
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Treg functionality by acetylation-mediated Foxp3 protein stabilization

Abstract: Regulatory T cells (Tregs) are a specific subset of lymphocytes that are critical for the maintenance of self-tolerance. Expression levels of the transcription factor Foxp3 have been causally associated with Treg differentiation and function. Recent studies show that Foxp3 can also be transiently expressed in effector T cells; however, stable Foxp3 expression is required for development of a functional Treg suppressor phenotype. Here, we demonstrate that Foxp3 is acetylated, and this can be reciprocally regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
318
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 333 publications
(336 citation statements)
references
References 39 publications
13
318
1
1
Order By: Relevance
“…Quantitative reverse transcriptase PCR RNA isolation, cDNA synthesis and quantitative PCR was performed as described (van Loosdregt et al, 2010). Forward Sox4 primer consisted of 5 0 -ggcctcgagctgggaatcgc-3 0 , reverse Sox4: 5 0 -gcccactcggggtcttgcac-3 0 ; forward syntenin: 5 0 -gcggcga gcggttccttgt-3 0 , reverse syntenin: 5 0 -tgctggattggcagggtttgcag-3 0 , b-2-microglobulin primers have been described (van Loosdregt et al, 2010).…”
Section: Western Blotsmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantitative reverse transcriptase PCR RNA isolation, cDNA synthesis and quantitative PCR was performed as described (van Loosdregt et al, 2010). Forward Sox4 primer consisted of 5 0 -ggcctcgagctgggaatcgc-3 0 , reverse Sox4: 5 0 -gcccactcggggtcttgcac-3 0 ; forward syntenin: 5 0 -gcggcga gcggttccttgt-3 0 , reverse syntenin: 5 0 -tgctggattggcagggtttgcag-3 0 , b-2-microglobulin primers have been described (van Loosdregt et al, 2010).…”
Section: Western Blotsmentioning
confidence: 99%
“…Forward Sox4 primer consisted of 5 0 -ggcctcgagctgggaatcgc-3 0 , reverse Sox4: 5 0 -gcccactcggggtcttgcac-3 0 ; forward syntenin: 5 0 -gcggcga gcggttccttgt-3 0 , reverse syntenin: 5 0 -tgctggattggcagggtttgcag-3 0 , b-2-microglobulin primers have been described (van Loosdregt et al, 2010).…”
Section: Western Blotsmentioning
confidence: 99%
“…SIRT1 has been shown to bind and decrease FoxP3 protein levels, possibly through its deacetylation. Accordingly, nicotinamide mediated SIRT1 inhibition increases both FoxP3 + protein levels and the relative proportion of FoxP3+ cells, resulting in an overall increased Treg suppressive function [42]. In line with these results, Yang and coworkers reported that resveratrol, a natural SIRT1 activator [43], depletes CD4 + CD25 + Tregs in tumor-bearing mice [44].…”
Section: Sirt1-dependent Deacetylation Of Foxp3 Leads To Its Degradationmentioning
confidence: 83%
“…Noteworthy, sirtuin activity has been shown to play a role in related processes such as cellular and organismal lifespan extension [6], [7], glucose homeostasis [63] and cellular differentiation [42], [58]. The work reviewed herein suggests that some of the pathological processes linked to metabolic disorders or aging may in fact be functionally linked to the immunomodulatory function of this family of metabolic sensors.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation